2019
DOI: 10.1186/s12864-019-6247-3
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid de novo transcriptome assembly of poinsettia (Euphorbia pulcherrima Willd. Ex Klotsch) bracts

Abstract: BackgroundPoinsettia is a popular and important ornamental crop, mostly during the Christmas season. Its bract coloration ranges from pink/red to creamy/white shades. Despite its ornamental value, there is a lack of knowledge about the genetics and molecular biology of poinsettia, especially on the mechanisms of color formation. We performed an RNA-Seq analysis in order to shed light on the transcriptome of poinsettia bracts. Moreover, we analyzed the transcriptome differences of red- and white-bracted poinset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 99 publications
0
27
0
Order By: Relevance
“…In a previous study (Vilperte et al, 2019), we observed higher expression of an anthocyanin-related GSTlike gene in the red poinsettia variety 'Christmas Feelings' than in its white counterpart 'Christmas Feelings Pearl'. To investigate whether a similar phenomenon is observed in other red and white poinsettia pairs, we performed RT-qPCRs for six pairs of red-bracted poinsettia varieties and their independently generated white mutants.…”
Section: Identi Cation and Characterization Of Bract1mentioning
confidence: 65%
See 3 more Smart Citations
“…In a previous study (Vilperte et al, 2019), we observed higher expression of an anthocyanin-related GSTlike gene in the red poinsettia variety 'Christmas Feelings' than in its white counterpart 'Christmas Feelings Pearl'. To investigate whether a similar phenomenon is observed in other red and white poinsettia pairs, we performed RT-qPCRs for six pairs of red-bracted poinsettia varieties and their independently generated white mutants.…”
Section: Identi Cation and Characterization Of Bract1mentioning
confidence: 65%
“…As GST genes occur in large gene families, we wanted to analyse whether the poinsettia GST gene was related to other GST genes involved in anthocyanin transport to the vacuole. Therefore, we computed a phylogenetic tree from the deducted amino acid sequences of 95 GST family members from our previously assembled poinsettia transcriptome (Vilperte et al, 2019), as well as the Bract1 and anthocyanin-related GSTs from other species (CkmGST3, LcGST4, VvGST4, PhAN9, PpRiant1, PpRiant2, AtGSTF11 and AtTT19). Nine GST classes were identi ed among the poinsettia GSTs: Tau, Theta, Lambda, Zeta, Phi, tetrachlorohydroquinone dehalogenase (TCHQD), glutathionyl hydroquinone reductase (GHR), dehydroascorbate reductase (DHAR) and eukaryotic translation elongation factor 1B-γ (Ef1Bγ).…”
Section: Bract Colouration Associated With a Deletion In The Bract1 Genementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, green leaves and red bracts occur concomitantly and accumulate different groups of pigments, i.e., chlorophylls and anthocyanins [ 53 , 61 ]. Several anthocyanin types have been identified in poinsettia bracts and are responsible for its colouration range [ 3 , 55 , 66 ]; however, molecular information is still limited for the species [ 28 , 72 ]. Nonetheless, genes responsible for the biosynthesis of the anthocyanin pathway have been intensively characterized in a range of species, with its regulation being highly dependent on R2R3-MYB regulatory genes and MYB-bHLH-WD40 (MBW) regulatory complexes [ 16 , 58 , 76 ].…”
Section: Introductionmentioning
confidence: 99%